2011
DOI: 10.1089/dia.2011.0002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Heat Modalities for Treating Delayed-Onset Muscle Soreness in People with Diabetes

Abstract: Muscle soreness following exercise was greatest in people with diabetes, and the best modality of the three studied to reduce this type of soreness was chemical moist heat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
1
22
0
4
Order By: Relevance
“…However, the heat pack treatment immediately after the strenuous exercise decreased PAIN. This result is supported by Petrofsky's study 23 regarding the attenuation of PAIN. They concluded that muscle soreness following exercise was greatest in people with diabetes, but was reduced by 20 minutes of moist heat.…”
Section: Perceived Painsupporting
confidence: 70%
See 2 more Smart Citations
“…However, the heat pack treatment immediately after the strenuous exercise decreased PAIN. This result is supported by Petrofsky's study 23 regarding the attenuation of PAIN. They concluded that muscle soreness following exercise was greatest in people with diabetes, but was reduced by 20 minutes of moist heat.…”
Section: Perceived Painsupporting
confidence: 70%
“…2 Heat is an easy and popular therapeutic procedure for soft tissues damage as well as joint and pain relief. 22,23 The effect of heat is to increase circulation, metabolism, and elasticity of connective tissues and thereby to reduce pain. 24 Heat modalities are commonly classified as superficial or deep heating agents.…”
Section: 13mentioning
confidence: 99%
See 1 more Smart Citation
“…A partir das categorias de análise formuladas, será disposta uma síntese dos achados associada à discussão de aspectos considerados de maior relevância. (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) , dois (menos de 1%) apresentaram considerações sobre as alterações osteomusculares (22)(23) e três (menos de 1%) se referiram às alterações vasculares relacionadas ao DM (24)(25)(26) . Os demais 13 artigos abordaram a atuação preventiva do fisioterapeuta, sendo que apenas um (menos de 1%) destacou estratégias destinadas à prevenção da doença (27) e 12 (35%) referiram-se à prevenção secundária, envolvendo a educação em saúde e a prescrição de exercícios aeróbicos e terapêuticos (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) .…”
Section: Materiais E Métodosunclassified
“…Avaliou-se a dor muscular tardia em indivíduos diabéticos e não diabéticos após a realização de exercícios globais, com ênfase para musculatura abdominal, dorsal e de flexores do quadril, e os efeitos da aplicação de diferentes modalidades de calor visando analgesia. Foi observada maior percepção da dor entre os indivíduos diabéticos a partir da escala visual analógica e a adoção de calor úmido apresentou-se como alternativa mais efetiva e segura para analgesia em relação à aplicação de envoltórios térmicos e compressas quentes (22) . Entre as síndromes dolorosas do ombro, a capsulite adesiva é frequentemente observada entre indivíduos com diabetes mellitus, chegando a apresentar uma prevalência em torno de 20% (45) .…”
Section: Alterações Osteomuscularesunclassified